Computational fluid dynamics-based disease transmission modeling of SARS-CoV-2 Intensive Care Unit. (2022) - Prajapati, Shivam; Mehta, Nishi; Chharia, Aviral; Upadhyay, Yogesh
Abstract: Covid-19 has become one of the most severe diseases causing acute respiratory problems and has killed millions of people worldwide. It was declared as the ongoing pandemic by the World Health Organization. It is an infectious virus which can be transmitted by sneezing, coughing and exhalation of air by any infected person. There are certain places having high chances of becoming contaminated like hospital rooms. In this context, we studied the transmission of Covid-19 particles in an ICU room. We have considered the combined effect of both of air-conditioning (AC) and ceiling fan in the room. The infected person can transmit the disease when under influence of fan and AC. The work highlights the flow of aerosol particles considering the combined effect as well as the individual effects of fan and AC. The results also emphasized that the aerosol particle flow have a promising application in sanitizing the room.